Increased maternal new‐onset psychiatric disorders after delivering a child with a major anomaly: a cohort study. (10th June 2020) - Rotberg, B.; Horváth‐Puhó, E.; Vigod, S.; Ray, J. G.; Sørensen, H. T.; Cohen, E.
Abstract : Background: The birth of a child with a major congenital anomaly may create chronic caregiving stress for mothers, yet little is known about their psychiatric outcomes. Aims: To evaluate the association of the birth of a child with a major congenital anomaly with subsequent maternal psychiatric risk. Methods: This Danish nationwide cohort study included mothers who gave birth to an infant with a major congenital anomaly ( n  = 19 220) between 1997 and 2015. Comparators were randomly selected mothers, matched on maternal age, year of delivery and parity ( n  = 195 399). The primary outcome was any new‐onset psychiatric diagnosis. Secondary outcomes included specific psychiatric diagnoses, psychiatric in‐patient admissions and redeemed psychoactive medicines. Cox models were used to estimate hazard ratios (HRs), adjusted for socioeconomic and medical variables. Results: Mothers of affected infants had an elevated risk for a new‐onset psychiatric disorder vs. the comparison group (adjusted HR, 1.16, 95% CI 1.11–1.22). The adjusted HR was particularly elevated during the first postpartum year (1.65, 95% CI 1.42–1.90), but remained high for years, especially among mothers of children with multiorgan anomalies (1.37, 95% CI 1.18–1.57). The risk was also elevated for most specific psychiatric diagnoses, admissions and medicines. Conclusions: Mothers who give birth to a child with a major congenital anomaly are at increased risk of new‐onset psychiatric disorders, especially shortly after birth and for mothers of children with more severe anomalies. Our study highlights the need to screen for mental illness in this high‐risk population, as well as to integrate adult mental health services and paediatric care.